Making graduation matter: initial evidence and implications for policy and research. Issue 9 (2nd September 2021) - Lin, Ching-Hui; Chen, Jyun-Hong; Borden, Victor M. H.
ABSTRACT: This study employs a quantitative method to understand the qualities of college experience that impact timely degree attainment. We specifically focus on how low socio-economic background students transition to and navigate the academic and social environment of a selective pubic research university. The study applies a longitudinal analysis to the institutional-level data from academic years 2006–2007 through 2012–2013 to examine college experiences germane to timely degree completion and level of academic performance. By focusing on student academic and social experiences transitioning into college, the study critically examines institutional policies and practices that influence degree attainment and the quality of further education outcomes. Implications of the results for institutional policies and practices are discussed.